IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) DENGAN PROSES FUZZIFIKASI DALAM PENILAIAN KINERJA DOSEN - Fifin - Sonata (Jurnal Teknologi Informasi dan Komunikasi, 2016)
The role of a lecturer in a University has a great influence on the learning process and development of the institution. Therefore , every universities should be able to minimize errors in the process of hiring new lecturers and existing lecturers who are teaching in the process of teaching.  The performance of lecturers should be evaluated in order to create a conducive atmosphere. Lecturer performance assessment is one of several method to observe and evaluate their works on Universities, particularly in the learning process. The Simple Additive weighting method (SAW) method combined with Fuzzi logic in assigning weights to each criteria is one appropriate method for assessing lecturer performance. Raw scores from each criteria will go through fuzzification process and normalization matrix that ultimately lead sorting at all alternatives. Results of sorting mechanism will help the university to evaluate the performance of lecturers in each semester or a certain period of time